What News Drive Variation in Swiss and US Bond and Stock Excess Returns? - Thomas Nitschka (Swiss Journal of Economics and Statistics, 2014)
Based on a vector autoregressive model (VAR), this paper shows that time variation in monthly excess returns on Swiss government bonds and stocks is predominantly driven by news of inflation and dividends, respectively. This finding is in marked contrast to US evidence which points to a more prominent role of excess return news. Variance decompositions based on estimates from threshold VARs show that US stock market evidence is consistent with the view that market participants put more weight on news of macroeconomic, i.e. cash-flow, risks in periods of exceptionally low real interest rates than in normal times.
Keywords: E44; G12; 330; bond return; news components; stock return; variance decomposition